Ultrastructural and some functional changes in tumor cells treated with stabilized iron oxide nanoparticles - Yurchenko, O.V.; Todor, I.N.; Khayetsky, I.K.; Tregubova, N.A.; Lukianova, N.Yu.; Chekhun, V.F. (Experimental Oncology, 2010)
The aim of this paper is to study the ultrastructure and some functional indexes of tumor cells treated with stabilized iron nanoparticles in vitro.